Keloid and Hypertrophic Scar Post-Excision Recurrence: A Retrospective Study - Azzahra, Alya Mutiara; Perdanakusuma, David Sontani; Indramaya, Diah Mira; Saputro, Iswinarno Doso (Jurnal Plastik Rekonstruksi, 2022)
Introduction : Abnormal scar recurrence can occur and often be greater than pre-excision because the recurrence rate is giving a high percentage. Data about keloid and hypertrophic scar recurrence are rarely found in Indonesia. Therefore, it is necessary to conduct research related to abnormal scar, aims to determine the incidence of abnormal scar recurrence to support future research by giving valuable data. Method : A retrospective descriptive study that evaluated post-excision abnormal scar patients from 2018 to 2020 using medical records. Result : The sixteen cases had varied by age with the highest number of presentations in the late adolescence (17-25 years) (31%). Comparison of male (56%) and female (44%) patients were 1.28:1. The distribution of patients with recurrence of abnormal scars based on the type of abnormal scar found that 11 patients (69%) had keloids and the rest had hypertrophic scars with a total of 5 patients (31%) with predominantly ear (38%). Strategies of therapy most commonly excision only (50%), followed by excision with steroid injection combination (31%). Conclusion: This exemplifies recurrence case in post-excision abnormal scar. Our findings indicate that there are differences in surgical strategy, such as wound closure techniques. Most of them were found with keloid scars and the incidence of recurrence was 11 cases and 5 cases experienced more than 1 recurrence. Furthermore, combination therapy, such as steroid injection, which is the most commonly used therapy after excision in this case, did not appear to prevent recurrence.